Vibration Analysis of a Low-Power Reduction Gear - Noga, S.; Markowski, T. (Проблемы прочности, 2016)
Free vibrations of a low-power reduction gear engaged with a hydraulic pump of the test rig are discussed. Vibration analysis is performed with the finite element representation and commercial ANSYS program. Vibration analysis of an examined system is conducted in the two stages. The natural frequencies of free transverse vibrations of the gears are first generated, and on the basis of the Campbell diagrams, the excitation speeds for several natural frequencies of examined gears are calculated. Then the free vibrations of a reduction gear are analyzed, and two computational cases are presented. In the first case, only the mass and geometry of all parts of the body are considered. In the second case, the mass of tooth gears is also taken into account. Based on the FE models, the first ten natural frequencies and natural mode shapes of a reduction gear are calculated. Then, these results are used to estimate the stress level in the walls of the body for a permissible acceleration value. As expected, smaller stress values for a permissible acceleration value are obtained for the second finite element model of the system. The problems discussed here can be helpful for engineers dealing with the dynamics of gear systems.